Risk factors for postpartum intrauterine device expulsion among women delivering at a tertiary Hospital in Uganda: a prospective cohort study - Muhumuza, Joy; Migisha, Richard; Ngonzi, Joseph; Kayondo, Musa; Mugyenyi, Godfrey Rwambuka (Contraception and Reproductive Medicine, 2021)
Background: Postpartum intrauterine device (PPIUD) use refers to intrauterine device (IUD) insertion after delivery but within 48 h of birth. In Uganda, the general use of modern methods of contraception is low with < 1% of the women adopting the IUD as a method of contraception. An important limiting factor to increased uptake of immediate postpartum IUD insertion may be its expulsion rates which vary widely. There is minimal documentation PPIUD expulsion rates and factors associated with PPIUD expulsion during puerperium in Uganda. Objective: We aimed to determine the proportion of TCu380A (copper) intrauterine devices expelled by 6 weeks postpartum, and identify risk factors for expulsion among women delivering at Mbarara Regional Referral Hospital (MRRH) in southwestern Uganda. Methods: We conducted a prospective cohort study from September 1, 2014 to January 31, 2015 at MRRH. We administered a structured questionnaire to all participants, to capture data on their baseline demographic, clinical and obstetric characteristics. We followed up women who accepted the PPIUD insertions at 6 weeks post insertion for any IUD expulsion. We fit multivariable log binomial regression models to identify risk factors for IUD expulsion. Results: We enrolled 167 women who had PPIUDs inserted. Of the144 women who returned at 6 weeks for follow up, 13 (9%; 95%CI:4.9–15%) of them had the IUDs expelled. In the multivariable model, the significant risk factors for PPIUD expulsion were: IUD insertion more than 10 min post-delivery (aRR 8.1, 95%CI 1.26–51.98, p = 0.027) and bloody lochia flow of ≥15 days (aRR 8.5, 95%CI 1.47–48.47, p = 0.017). Conclusion: The cumulative expulsion rate of postpartum IUDs among women delivering at MRRH was low and comparable to expulsion rates in interval insertions. Longer duration from delivery to IUD insertions and longer duration of bloody lochia flow were key risk factors for postpartum IUD expulsion. More emphasis should be put on prenatal counseling for postpartum family planning to allow for postplacental IUD insertions, which are associated with lower expulsion rates.
Keywords: Copper intrauterine device; Intrauterine device; Intrauterine device expulsion; Postpartum contraception; Postpartum intrauterine device; Postplacental intrauterine device; TCu380A intrauterine device